Енергоефективність будинку при поелементному утепленні - Сахновська, Світлана; Жирноклєєв, Вячеслав (Видавництво Національного університету «Львівська політехніка», 2009)
In this article are presented results of experimental researches temperature – moist regime of nine-storeyed building with large blocks, analyzed variants of barriering constructions warming with the purpose of providing energyefficient normative values.
Keywords: енергоефективні; потепління; температурний режим; енергоефективність; тепловитрати; утеплення будинку; energyefficient; warming; temperature – moist regime